Ultrasound-Guided Evaluation of the Local Anesthetic Spread Parameters Required for a Rapid Surgical Popliteal Sciatic Nerve Block. Issue 6 (1st October 2010) - Morau, Didier; Levy, Frank; Bringuier, Sophie; Biboulet, Philippe; Choquet, Olivier; Kassim, Michèle; Bernard, Nathalie; Capdevila, Xavier
Abstract : Background: The ideal spread of local anesthetic (LA) solution around the sciatic nerve during a popliteal block remains unclear. We tested the hypothesis that a circumferential spread of LA and/or intraneural injection could lead to rapid surgical block. Methods: Patients (n = 100) scheduled for foot or ankle surgery underwent popliteal sciatic nerve block using nerve stimulation according to Borgeat's technique and injection of ropivacaine (0.5 mL/kg). Sensory and motor blockades were assessed on the tibial nerve (TN) and common peroneal nerve (CPN) at 5, 15, and 30 mins after completion of the block and in the recovery room. A successful block was defined as a complete sensory block in TN and CPN. Changes in cross-sectional and longitudinal surfaces and diameters and the characteristics of LA spread around the nerve were noted using ultrasound. A suspected intraneural injection was defined as a 15% increase in the surface area or anteroposterior diameter of the nerve. Patients were followed up on days 1 and 7 after surgery. Results: Successful block was noted in 57% of patients at 30 mins and in 88% of patients in the recovery room. A circumferential spread of LA occurred in 47% of patients and 53% had noncircumferential spread. Complete sensory block was significantly higher in the group that had a circumferential spread (73% vs 43%, P = 0.035) only at 30 mins. In the postoperative care unit, there was no difference among the groups. Separated circumferential spreads around TN and CPN were noted in 12% of patients. All of these patients had a complete sensory and motor blockade at 15 mins. Concerning intraneural injection, only the change in the anteroposterior diameter on a 6-cm length of nerve was associated with a higher success and faster onset block at 5 ( P = 0.008), 15 ( P = 0.02), and 30 ( P = 0.05) mins. There were no clinically detectable nerve injuries at follow-up. Conclusion: For popliteal sciatic nerve block, circumferential spread of LA, and separation of the nerve into its 2 components are associated with rapid surgical block.